A WHO global framework to guide investigations into origins of potentially epidemic and pandemic pathogens - The Scientific Advisory Committee for the Origins of Novel Pathogens (SAGO); WHO SAGO Secretariat (Nature Research, 2025)
In outbreak situations involving a novel pathogen timely and coordinated response is crucial. The WHO Scientific Advisory Group for the Origins of Novel Pathogens recently released a global framework to guide future scientific investigations into the origin of emerging pathogens.